(untitled) (Bangladesh Journal of Pharmacology, 2016)
The main purpose of the present study was to examine the antitumor and apoptotic effects of lactucin in HL-60 human leukemia cancer cells. MTT assay was used to examine the cytotoxic effects of lactucin while as phase contrast, fluorescence and transmission electron microscopy techniques were used to evaluate the apoptotic effects of lactucin in these cells. Flow cytometry was used to assess the effects of lactucin on cell cycle phase distribution. The results indicate that lactucin induced potent, time and dose-dependent antitumor effects. The microscopic techniques showed that lactucin induced characteristic features of apoptosis including cell shrinkage, membrane blebbing, appearance of vacuoles, swelling of mitochondria and endoplasmic reticulum. Viable cells are stained green, early apoptotic cells are stained yellow, while as late apoptotic cells are stained reddish orange. Flow cytometry revealed that lactucin induced sub-G1 cell cycle arrest. Video Clips of Methodology: Phase contrast microscopy: One Full Screen Alternate Two Full Screen Alternate Three Full Screen Alternate Four Full Screen Alternate Five Full Screen Alternate Six Full Screen Alternate Seven Full Screen Alternate Eight Full Screen Alternate Nine Full Screen Alternate